Determinants of Household Savings: An Empirical Evidence from the OECD Member Countries - Hunt, Ethan; Jeon, Hyungjoon; Lee, Sang (Business and Economic Research, 2021)
<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Using the data from the 36 OECD member countries over a time period of 1970-2017, we study variations in household saving rate across the countries through the lens of the socio-economic and -demographic shifts over time. In addition to traditional determinants of household saving such as life expectancy, education, average number of children born per woman over a lifetime, and household debts, we examined changes in the socio-economic and -demographic conditions that are conducive to the human capital value of female labor force and thus female employment opportunities. We have identified that the narrower is the gap between genders in higher education attainment and employment, the higher is the household saving rate. Our empirical findings also suggest that both giving childbirth at an old age and preferential income tax rates for households with children are negatively affecting the household saving rate.